Denture stomatitis associated with small-colony variants of Staphylococcus aureus: a case report - Katarzyna Garbacz; Ewa Kwapisz; Maria Wierzbowska (BMC, 2019)
Abstract Background The small-colony variants (SCVs) of Staphylococcus aureus were isolated from persistent and recurrent infections, especially after placement of medical devices having direct contact with human tissues. The emergence of SCVs is a survival strategy of S. aureus which enables them to hide inside host's cells and induces a less severe immune response than to wild-type S. aureus. However, contrary to other medical devices, dental prosthesis as a surface potentially colonized by SCVs of S. aureus has not been examined thus far. We reported the first case of SCVs - S. aureus infection in denture wearer. Case presentation A 62-year-old woman with a complete removable acrylic denture presented extensive elevated erythematous lesions on the palate, compatible with denture stomatitis. The patient had a history of arterial hypertension, cigarette smoking and wearing denture at night. The fungal colonies, identified as Candida albicans, were cultured on Sabouraud agar. From three swabs (from hard palate mucosa, denture surface and angular cheilitis lesions) were cultured of pinpoint, clear, non-pigmented, and non-haemolytic colonies on Columbia agar. The small colonies turned out to be Gram-positive cocci, catalase-, Pastorex Staph Plus -, and clumping factor-positive, and oxidase-negative. Suspected phenotypically SCVs forms were definitively identified as S. aureus based on PCR amplification of species specific nuc and coa genes. Methicillin-resistance was verified by mecA gene detection. The isolates turned out to be susceptible to methicillin (MSSA) and resistant to gentamicin. The isolate was identified as menadione-auxotrophic variant. Conclusions This case demonstrated that oral cavity in denture wearers may be a reservoir of small-colony variants of S. aureus, besides C. albicans. The prevalence of these bacteria and their role in the pathogenesis of oral diseases are not understood. Due to problems with their detection and identification, the true prevalence of oral SCVs may be underestimated.